Effect of Technological Process on True Retention Rate of Eicosapentaenoic and Docosahexaenoic Acids, Lipid Oxidation and Physical Properties of Canned Smoked Sprat (Sprattus sprattus) - Zdzisław Domiszewski; Sylwia Mierzejewska (International Journal of Food Science)
In connection with the severe deficiencies of EPA and DHA in the human diet, the industry should provide inexpensive fish products that are characterized by the appropriate lipid quality. The influence of the technological process on true retention rate of EPA and DHA, indicators of lipid oxidation and physical properties, of canned smoked sprat in oil was investigated. It was assumed that the double dose of heat during the technological process (smoking/sterilization) can significantly affect the quality of lipids. The study was carried out on fresh fish and after frozen storage. After smoking, the percentage of EPA and DHA in lipids did not change significantly, while the content of these acids per wet weight (g/100 g) increased by about 20%. During smoking, a faster increase in oxidation products was observed in frozen fish (increase by 22%-36%) than in fresh fish (increase by 31%-54%). Sterilization caused EPA and DHA to be “regrouped” from the fish to the oil rather than their physical losses. After sterilization, the fish retained 70%-77% EPA and DHA content (the rest passed into the oil). EPA and DHA losses were 8.5% higher in canned products obtained from frozen fish compared to fresh fish. True retention should be used to assess changes in EPA and DHA content in fish after sterilization (and not the expression of EPA and DHA content in % or g/100 g). A better indicator of changes in the physical parameters of canned fish after sterilization is the analysis of the proportion of the water layer rather than mass measurement. Despite the double dose of heat that occurred during the canned sprat production process, the peroxide value in fish and in oil did not exceed 10 (mEqO2/kg of lipid) and p-anisidine value did not exceed 20. This means that these lipids were characterized by good quality.